Pengaruh Lumpur Sawit terhadap Pertumbuhan Kelapa Sawit pada Tanah Gambut di Pre Nursery - pratama, bima candra (Jurnal Sains Pertanian Equator, 2015)
ABSTRACT This research aims to determine the effect of solid decanter best on the growth of palm oil on peat soil, especially pre nursery. This research was conducted in Paal Lima, West Pontianak Districts, Pontianak City, which taken about 3 months. This research using a completely randomized design which consists of a single factor, that sludge, with six treatments, four replications, and ten samples of plants. Variable observed in this research include the persentage of life of the seedlings, root volume and dry weight of plants. The results showed that the treatment was highly significant to the variable of root volume and dry weight of plants, but no real effect on the percentage of life of the seedlings variable. The best effects is given by solid decanter 50% with the highest average on root volume variable and dry weight of plants variable. Keywords : Palm oil, peat, pre nursery, solid decanter